Enhancing Junior High School Students’ Speaking Skills: An Evaluation of the Fishbowl Strategy’s Effectiveness - Gulo, Arisonia Elisabeth Yohana; Simanjuntak, Debora Chaterin (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
This study explores the extent to which junior high school students’ speaking abilities can be developed through the use of the Fishbowl strategy. The study employs a comparative research design with a quantitative methodology, wherein one group is taught conventional methods, and the other group is taught using the Fishbowl strategy. Data was collected through pretest and posttest assessments and a questionnaire to measure students’ attitudes toward the strategy. The results indicate that there is a significant effect in students’ speaking skills after using the Fishbowl strategy, as evidenced by the average n-gain value of the experimental group. Analysis shows a significant difference between students taught using the fishbowl strategy and students taught using the conventional method, with a significance value of 0.030. The survey results also revealed that the majority of students reported increased confidence and motivation to speak English after using the Fishbowl strategy as 64% of respondents agreed that they had become more confident, while 51% stated that they were more motivated to speak English after using this strategy. In conclusion, the Fishbowl strategy is effective in improving students’ speaking skills, confidence, and motivation in speaking English in junior high school.